Are You Satisfied? Citizen Feedback and Delivery of Urban Services - Deichmann, Uwe; Lall, Somik V. (World Bank, Washington, DC, 2014)
Citizen feedback is considered an effective means for improving the performance of public utilities. But how well does such information reflect the actual quality of service delivery? Do so-called scorecards or report cards measure public service delivery accurately, or do personal and community characteristics have a significant impact on residents' assessment of service quality? Deichmann and Lall investigate these questions using newly available household survey data on access to and satisfaction with selected public services in two Indian cities-Bangalore and Jaipur. They develop a framework where actual levels of services received, as well as expectations about service performance, influence a household's satisfaction with service delivery. The authors find that satisfaction increases with improvements in the household's own service status, a finding that supports the use of scorecard initiatives. But the results also suggest that a household's satisfaction is influenced by how service quality compares with that of its neighbors or peers and by household level characteristics such as welfare and tenure status. This implies that responses in satisfaction surveys are at least in part determined by factors that are unrelated to the service performance experienced by the household.